Effects of Photons Irradiation on 18F-FET and 18F-DOPA Uptake by T98G Glioblastoma Cells - Pasi, Francesca; Persico, Marco G.; Marenco, Manuela; Vigorito, Martina; Facoetti, Angelica; Hodolic, Marina; Nano, Rosanna; Cavenaghi, Giorgio; Lodola, Lorenzo; Aprile, Carlo (Frontiers in Neuroscience, 2020)
The differential diagnosis between brain tumors recurrence and early neuroinflammation or late radionecrosis is still an unsolved problem. The new emerging magnetic resonance imaging, computed tomography, and positron emission tomography diagnostic modalities still lack sufficient accuracy. In the last years, a great effort has been made to develop radiotracers able to detect specific altered metabolic pathways or tumor receptor markers. Our research project aims to evaluate irradiation effects on radiopharmaceutical uptake and compare the kinetic of the fluorinate tracers. T98G glioblastoma cells were irradiated at doses of 2, 10, and 20 Gy with photons, and 18F-DOPA and 18F-FET tracer uptake was evaluated. Activity and cell viability at different incubation times were measured. 18F-FET and 18F-DOPA are accumulated via the LAT-1 transporter, but 18F-DOPA is further incorporated, whereas 18F-FET is not metabolized. Therefore, time-activity curves (TACs) tend to plateau with 18F-DOPA and to a rapid washout with 18F-FET. After irradiation, 18F-DOPA TAC resembles the 18F-FET pattern. 18F-DOPA activity peak we observed at 20 min might be fictitious, because earlier time points have not been evaluated, and a higher activity peak before 20 min cannot be excluded. In addition, the activity retained in the irradiated cells remains higher in comparison to the sham ones at all time points investigated. This aspect is similar in the 18F-FET TAC but less evident. Therefore, we can hypothesize the presence of a second intracellular compartment in addition to the amino acidic pool one governed by LAT-1, which could explain the progressive accumulation of 18F-DOPA in unirradiated cells.